2022
DOI: 10.3390/polym14061242
|View full text |Cite
|
Sign up to set email alerts
|

Tribological and Antibacterial Properties of Polyetheretherketone Composites with Black Phosphorus Nanosheets

Abstract: Over the past few decades, polyetheretherketone (PEEK) artificial bone joint materials faced problems of poor wear resistance and easy infection, which are not suitable for the growing demand of bone joints. The tribological behavior and wear mechanism of polyetheretherketone (PEEK)/polytetrafluoroethylene (PTFE) with black phosphorus (BP) nanosheets have been investigated under dry sliding friction. Compared with pure PEEK, the COF of PEEK/10 wt% PTFE/0.5 wt% BP was reduced by about 73% (from 0.369 to 0.097) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Black phosphorus inhibited S. aureus by only the generation of ROS [92]. Similarly, the bacterial reduction with ZrO 2 nanoparticles on the surface stemmed from the formation of ROS.…”
Section: The Mechanisms Of the Antibacterial Effect Of Modified Peekmentioning
confidence: 94%
See 3 more Smart Citations
“…Black phosphorus inhibited S. aureus by only the generation of ROS [92]. Similarly, the bacterial reduction with ZrO 2 nanoparticles on the surface stemmed from the formation of ROS.…”
Section: The Mechanisms Of the Antibacterial Effect Of Modified Peekmentioning
confidence: 94%
“…The first step includes powder mixing using a liquid medium such as ethanol to obtain a homogeneous mixture. PEEK powder or blends of PEEK and reinforcements in powder form are dispersed in the medium [92]. The second step includes heating above the melting temperature (PEEK melting temperature: ∼343 • C) for injection molding, compression molding, selectively laser sintering, cold pressing sintering, and twin-screw extrusion [51,54,144,149,150] to obtain composite materials or electrophoretic deposition for composite coatings [83].…”
Section: Coating With Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“… 144 A similar study was also conducted by Sun et al where the group demonstrated that a composite made of polyetheretherketone (PEEK)/polytetrafluoroethylene (PTFE) with black phosphorus (BP) nanosheets was able to increase the wear resistance and antimicrobial property while being much less cytotoxic. 145 Recently, Fang et al have reported a phototherapeutic system by combining polydopamine (PDA)–black phosphorus nanosheets (BP NSs)/ZnO nanowires (NWs) on titanium (Ti) substrates which exhibited outstanding antibacterial properties against biofilm-causing bacteria. 146 …”
Section: D-nanomaterial-based Nanocoatingmentioning
confidence: 99%